Survival Strategy and Efforts to Increase Sales in Small and Medium Enterprises in The Culinary Sector - Sulistiati, Dwi Febry; Moeljono, Moeljono (PT. Riset Press International, 2023)
This study aims to identify the level of sales at Omah Sate Tlogo Berkah. Efforts to increase sales at Omah Sate Tlogo Berkah. Knowing strategies to increase sales at Omah Sate Tlogo Berkah. Approach using qualitative methods. The purpose of this study is to get a real picture of the strategy used by Omah Sate Tlogo Berkah. The results of the study also show that there are supporting factors for the application of the marketing mix to the sales of Omah Sate Tlogo Berkah, and the supporting factors are capital, labor, raw materials, marketing and culture. While the inhibiting factors for the application of the marketing mix to the sale of Omah Sate Tlogo Berkah are the lack of people's purchasing power. The conclusion from this study is that Omah Sate Tlogo Berkah has implemented a marketing mix strategy using the 4P variables, namely product, price, place, and promotion, which is able to increase sales volume at Omah Sate Tlogo Berkah.